Interception loss, throughfall and stemflow by Larrea divaricata: The role of rainfall characteristics and plant morphological attributes - Magliano, Patricio Nicolás (2019)
Rainfall partitioning into interception loss, throughfall and stemflow affects the amount and the spatial heterogeneity of water entering into the soil at the patch scale, strongly controlling net primary productivity of drylands. In this paper, we explored rainfall partitioning and its biophysical controls in Larrea divaricata (jarilla), one of the most abundant shrubs in the Dry Chaco rangelands (Argentina). On average, interception loss, throughfall and stemflow accounted for 9.4, 78.6 and 12.0% of total rainfall, respectively. Interception loss proportion decreased with the increment of rainfall event size and intensity, whereas throughfall proportion showed the opposite pattern. Stemflow proportion increased with the increment of rainfall event size but presented different relations with rainfall event intensity. The increment of rainfall event intensity increased the stemflow in small events (<20 mm), but decreased it in large events (>20 mm). Stemflow increased in plants with higher angles of insertion of stems (measured at 50 and 100 cm from soil surface; p < .05 and p < .01, respectively), but decreased in plants with larger canopy areas (p = .01). Spatial distribution of throughfall (coefficient of variation) decreased with the increment of rainfall event size and intensity. L. divaricata presented more stemflow generation and fewer interception losses than other similar woody species. Our findings help to understand the key role of vegetation canopy affecting the amount of water entering into the soil in drylands.